2018
DOI: 10.20885/ejem.vol10.iss1.art1
|View full text |Cite
|
Sign up to set email alerts
|

Robust approach for efficiency measurement of employee performance under profit sharing system

Abstract: This study estimates the efficiency of employees' performances under profit sharing system using data envelopment analysis (DEA). This method is one of the most common methods used in efficiency measurement analysis. However, a robust approach is used to deal with the complexity of the traditional DEA estimators. Robust Data Envelopment Analysis (RDEA) is very useful when outliers contaminate the data. The sample includes five divisions which cover as many as 102 employees of a shipping company in Malaysia are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In order to see the comparison of the empirical results from the traditional DEA and RDEA approaches it could be seen in figure 2, figure 3, and figure 4 for all the numbers of replication. DEA model of input-oriented indicated that inefficient units needed to reduce their inputs proportionally to achieve efficient performance when the output variables were constant (Mahmudah & Lola, 2018;Simar & Wilson, 2007). RDEA produced a similar value of the average efficiency score for all the number of replications, which was 0.926.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In order to see the comparison of the empirical results from the traditional DEA and RDEA approaches it could be seen in figure 2, figure 3, and figure 4 for all the numbers of replication. DEA model of input-oriented indicated that inefficient units needed to reduce their inputs proportionally to achieve efficient performance when the output variables were constant (Mahmudah & Lola, 2018;Simar & Wilson, 2007). RDEA produced a similar value of the average efficiency score for all the number of replications, which was 0.926.…”
Section: Discussionmentioning
confidence: 95%
“…Mahmudah & Lola applied RDEA in estimating employee's performance when they received profit sharing from the company by using 102 samples in a shipping company in Malaysia. The results suggested that the robust approach in data envelopment analysis provided better accuracy of the bias-corrected efficiency scores than the traditional DEA (Besstremyannaya et al, 2015;Mahmudah & Lola, 2018). There were 34 provinces in Indonesia with a total of 147,513 elementary schools which consisted of 132,609 public elementary schools and 14,904 private elementary schools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation